Nanomedicines Reprogram Synovial Macrophages by Scavenging Nitric Oxide and Silencing CA9 in Progressive Osteoarthritis. Issue 11 (7th February 2023) - Yan, Yi; Lu, An; Dou, Yun; Zhang, Zhen; Wang, Xiang‐Yu; Zhai, Lin; Ai, Li‐Ya; Du, Ming‐Ze; Jiang, Lin‐Xia; Zhu, Yuan‐Jun; Shi, Yu‐Jie; Liu, Xiao‐Yan; et al.
Abstract: Osteoarthritis (OA) is a progressive joint disease characterized by inflammation and cartilage destruction, and its progression is closely related to imbalances in the M1/M2 synovial macrophages. A two‐pronged strategy for the regulation of intracellular/extracellular nitric oxide (NO) and hydrogen protons for reprogramming M1/M2 synovial macrophages is proposed. The combination of carbonic anhydrase IX (CA9) siRNA and NO scavenger in "two‐in‐one" nanocarriers (NAHA‐CaP/siRNA nanoparticles) is developed for progressive OA therapy by scavenging NO and inhibiting CA9 expression in synovial macrophages. In vitro experiments demonstrate that these NPs can significantly scavenge intracellular NO similar to the levels as those in the normal group and downregulate the expression levels of CA9 mRNA (≈90%), thereby repolarizing the M1 macrophages into the M2 phenotype and increasing the expression levels of pro‐chondrogenic TGF‐ β 1 mRNA (≈1.3‐fold), and inhibiting chondrocyte apoptosis. Furthermore, in vivo experiments show that the NPs have great anti‐inflammation, cartilage protection and repair effects, thereby effectively alleviating OA progression in both monoiodoacetic acid‐induced early and late OA mouse models and a surgical destabilization of medial meniscus‐induced OA rat model. Therefore, the siCA9 and NO scavenger "two‐in‐one" delivery system is a potential and efficient strategy for progressive OA treatment. Abstract : The carbonic anhydrase IX siRNA and nitric oxide (NO) scavenger in "two‐in‐one" nanocarriers is developed for progressive osteoarthritis (OA) therapy. A two‐pronged strategy is proposed for the regulation of intracellular/extracellular NO and hydrogen protons for reprogramming M1/M2 synovial macrophages, which holds promising application prospects for clinical translation of progressive OA treatment.